Marcación de aceite de tung con 131I - Correia, R.J.; Mitta, A.E.A. (Comisión Nacional de Energía Atómica (CNEA), 1975)
Fil:Correia, R.J. Comisión Nacional de Energía Atómica (CNEA). República Argentina